Acute kidney injury after myeloablative cord blood transplantation in adults: the efficacy of strict monitoring of vancomycin serum trough concentrations. Issue 2 (20th December 2012) - Mae, H.; Ooi, J.; Takahashi, S.; Kato, S.; Kawakita, T.; Ebihara, Y.; Tsuji, K.; Nagamura, F.; Echizen, H.; Tojo, A.
Abstract Background Acute kidney injury (AKI) is a common medical complication after myeloablative allogeneic stem cell transplantation (SCT). We have previously performed a retrospective analysis of AKI after cord blood transplantation (CBT) in adults, and found that the maximum of vancomycin (VCM) trough levels were significantly higher in patients with AKI. Following these results, we have monitored VCM serum trough concentrations more strictly, to not exceed 10.0 mg/L, since 2008. Methods In this report, we performed an analysis of AKI in a new group of 38 adult patients with hematological malignancies treated with unrelated CBT after myeloablative conditioning between January 2008 and July 2011. Results Cumulative incidence of AKI at day 100 after CBT was 34% (95% confidence interval 19–50). The median of the maximum value of VCM trough was 8.8 (4.5–12.2) mg/L. In multivariate analysis, no factor was associated with the incidence of AKI. No transplant‐related mortality was observed. The probability of disease‐free survival at 2 years was 83%. Conclusion These findings suggest that strict monitoring of VCM serum trough concentrations has a beneficial effect on outcomes of CBT.